Merkle-Damgård as the Foundation of Hash Cryptography: A Study of Advantages and Limitations - Tri Ade Nia; Rudyanto Ompungsunggu; Arrant Ardi Sianipar; Jesimanta, Jesimanta; Yoramo Waruwu (SEAN Institute, 2024)
The Merkle-Damgård algorithm is a key foundation in many cryptographic hash functions, including MD5, SHA-1, and SHA-256. This article discusses the working mechanism of the Merkle-Damgård structure, its advantages in maintaining data integrity, as well as the weaknesses that make it vulnerable to certain attacks. The study uses a quantitative approach through simulation and testing of Merkle-Damgård-based hash functions. This structure allows a variable-length input to be converted into a fixed-length hash output through a block-based iterative process and compression function. The results show that this algorithm successfully converts plaintext into a unique hash according to the hashing principle, as shown in both binary and ASCII representations. While effective in many digital security applications, this research highlights the importance of mitigating against potential attacks to improve the security of Merkle-Damgård-based algorithms.